(untitled) (Innovative Technology and Management Journal, 2020)
With the Coronavirus Disease 2019 (COVID-19) outbreak, closure of factories and manufacturing hubs produced a drastic effect on the production and labor sector. Through the previously going industrial revolution, additive manufacturing (AM), which is considered to be one of the disruptive technologies, must be looked into consideration and be studied for its applications as the new normal to comply with the current demand for manufacturing. It disrupts how the manufacturing process is done and the underlying factors that can be substantially reduced, such as time spent and resource consumption in manufacturing. This paper provides a review of worldwide trends and current local government initiatives in 3D printing (3DP). Policy recommendations are discussed with respect to the governing factors that must be considered under a new normal.